THE TRANSLATION STRATEGIES ON ADDRESS TERMS IN LOVE ROSIE MOVIE - Syahron Lubis; Nabila Mei Shara (ELP (Journal of English Language Pedagogy), 2022)
This research aims to find out the types of address terms found in the Love Rosie movie and to find out how the address terms are translated into Bahasa Indonesia. In collecting the data in this research, the researcher used the descriptive qualitative method. The data collected in this research were from the data sources which are the Love Rosie movie and the movie manuscript. The types of the address terms theories by Wardhaugh (2006: 271), Simatupang (2000: 77), and Larson (1984: 121), and the translation procedures theory by Vinay and Dalbernet (2000: 84-93) were used in analyzing the data in this research. This research used data analysis techniques by Miles, Huberman, and Saldana (2014). There were 65 data collected in this research. The findings of this research showed two main points. (1) There were 5 types of address; 6 data of pronouns, 17 data of kinship, 10 data of titles, 22 data of names, and 10 data of endearments. (2) There were six translation procedures applied in translating the address terms; 19 data translated by applying literal translation, 17 data by applying borrowing, 13 data by applying transposition, 1 data by applying modulation, 1 data by applying equivalence, and 14 data by applying adaption. Based on the data analysis and the findings, it can be concluded that the types of address terms found in the Love Rosie movie are in the form of pronouns, kinship, titles, names, and endearments. There are 6 address terms in the form of pronouns, 17 address terms in the form of kinship, 10 address terms in the form of titles, 22 address terms in the form of names, and 10 address terms in the form of endearments. Then, the translation procedures applied by the translator in translating the address terms in Love Rosie movie are using Vinay and Dalbernet’s (2000: 84-93) theory which are literal translation, borrowing, transposition, calque, modulation, equivalence, and adaptation. There are 18 address terms are translated by applying literal translation which is the most commonly used procedure by the translator, 17 address terms by applying borrowing, 12 address terms by applying transposition, 1 address term by applying modulation, 1 address term by applying equivalence, and 16 address terms by applying adaptation.